Time-varying risk premia, volatility, and technical trading rule profits: Evidence from foreign currency futures markets - Kho, Bong-Chan (Journal of Financial Economics, 1996)
This paper re-examines the efficiency of foreign currency futures markets by evaluating the role of time-varying risk premia and volatility in explaining technical trading rule profits. The results show that large parts of the technical rule profits can be explained by the time-varying risk premia estimated from a general model for the conditional CAPM; The bootstrap distributions for the profits under the null model average one-third to one-half of the actual profits and enclose the actual profits well within the 90% confidence intervals. Time-varying conditional volatility explains an additional 10% of the profits.